Inclusive Leadership and Employee Creativity in the Era of Diversity Workforce - Alaika Zinatul Hayat (PT. AVID MEDIA INDONESIA, 2026)
This study aims to examine the effect of inclusive leadership on employee creativity in the context of diversity workforce. The method used is mixed method, involving 285 employee respondents from various backgrounds of generation, gender, education, and ethnicity. Quantitative data were analyzed using linear regression and structural equation modeling (SEM) with bootstrapping mediation test, while qualitative data were obtained through in-depth interviews to strengthen the interpretation of findings. The results showed that inclusive leadership has a positive and significant effect on employee creativity, both directly and indirectly through psychological safety. Empirically, the R² value of 0.39 indicates that inclusive leadership is able to explain 39% of the variation in employee creativity. This finding confirms that inclusive leaders are able to create a safe, fair, and participatory work climate so that employees are encouraged to express innovative ideas. This research provides theoretical contributions by expanding contemporary leadership literature, especially the inclusiveness dimension, as well as practical contributions in the form of guidance for organizations in optimizing the potential of workforce diversity to increase creativity-based competitiveness